The Influence of Motivation Leadership and Work Discipline on Employees Work Spirit at Astagina Resort Villa and Spa Kuta Bali - Wartana, I Made Hedy; Sumerta, I Ketut Eli (Jurnal Manajemen Pelayanan Hotel, 2023)
This research aims to determine the effect of motivation (X1) leadership (X2) and work discipline (X3) onemployee morale (Y) at Astagina Resort Villa and Spa Kuta Bali. The respondents used in this research were allemployees of Astagina Resort Villa and Spa Kuta Bali with a total of 89 respondents. The data used in theresearch is primary data, namely from the results of questionnaire answers, then the results of thequestionnaire answers are tested using validity and reliability tests followed by classical assumption tests andmultiple linear regression analysis. The research results show that motivation (X1) has a positive andsignificant effect on employee morale at Astagina Resort Villa and Spa Kuta Bali. This is proven by the t-count= 2.783 > t-table = 1.66 and the Sig. = 0.007<0.05. This means that motivation has a positive and significantinfluence on employee morale. Leadership (X2) has a positive and significant effect on employee morale atAstagina Resort Villa and Spa Legian Bali. This is proven by the t-count = 4.097 > t-table = 1.66 and the Sig. =0.000<0.05. This means that leadership has a positive and significant effect on employee morale. Workdiscipline (X3) has a positive and significant effect on employee morale at Astagina Resort Villa and Spa KutaBali. This is proven by the t-count value = 4.286 > t-table = 1.66 and the Sig value. = 0.000<0.05. This meansthat work discipline has a positive and significant effect on employee performance.Keywords: Motivation, Leadership, Work Discipline, Employee Work Spirit.